Hospital crowding and patient outcomes - Wolfgang Frimmel; Felix Glaser; Gerald J. Pruckner (Johannes Kepler University of Linz, Department of Economics, 2025)
Using high-quality administrative data from Upper Austria, we analyze the effect of hospital crowding on patients' short- and medium-term healthcare utilization and labor market outcomes. Focusing on acute inpatient diagnoses, we exploit idiosyncratic variation in daily diagnosis-related hospital occupancy rates to estimate the causal effect of hospital crowding. We find that higher crowding levels reduce hospital care intensity, as reflected in fewer medical services provided, lower hospital expenditures, and earlier discharges. Despite these changes, quality of care indicators, including readmissions and mortality, remain unaffected. However, no significant effects are observed either on inpatient and outpatient healthcare utilization in the short- and medium-term or on patients' labor market outcomes following initial hospitalization. These results suggest that crowding-induced differences in hospital care do not lead to changes in patients' health or economic situations over the medium term.
Keywords: I10; I12; I14; I31; J20; 330; Hospital Crowding; Health Care Utilization; Labor Market